Disconnected relationships between primary care and community-based health and social services and system navigation for older adults: a qualitative descriptive study - Valaitis, Ruta (BMC Fam Pract, 2020)
BACKGROUND: There are gaps in knowledge and understanding about the relationships between primary care and community-based health and social services in the context of healthy aging at home and system navigation. This study examined provider perspectives on: a) older adults’ health and social needs; b) barriers to accessing services; c) the nature of relationships between primary care and health and social services; and d) ways to facilitate primary care and health and social services navigation to optimize older adults’ health. METHODS: Four focus groups were conducted involving providers (n = 21) in: urban primary care clinics and health and social services organizations serving older adults in Hamilton, Ontario, Canada. Purposive sampling was employed to recruit community health and social services managers, directors or supervisors and primary health care providers in a Family Health Team via email. RESULTS: Health and social services needs were exacerbated for community-dwelling older adults with multiple chronic conditions. Strong family/caregiver social support and advocacy was often lacking. Access barriers for older adults included: financial challenges; lack of accessible transportation; wait times and eligibility criteria; and lack of programs to address older adults’ needs. Having multiple providers meant that assessments among providers and older adults resulted in contradictory care pathways. Primary care and health and social services linkages were deficient and complicated by poor communication with patients and health literacy barriers. Primary care had stronger links with other health services than with community-based health and social services; primary care providers were frustrated by the complex nature of health and social services navigation; and care coordination was problematic. Health and social services referred older adults to primary care for medical needs and gathered patient information to gauge program eligibility, but not without challenges. CONCLUSIONS: Results point to strategies to strengthen primary care and health and social services system navigation for older adults including: using a person-focused approach; employing effective primary care and health and social services communication strategies; applying effective system navigation; building trust between primary care and health and social services providers; advocating for improved program access; and adapting services/programs to address access barriers and meet older adults’ needs.